Ecodharma: Buddhist teachings for the ecological crisis - Loy, David (Wisdom Publications, 2018)
On a precipice -- Is climate change the problem? -- Is the eco-crisis also a Buddhist crisis? -- What are we overlooking? -- Is it the same problem? -- What if it's too late? -- What shall we do? -- A prodigal species